y=8x+12

Rewrite the equation as 8x+12=y.

8x+12=y

Subtract 12 from both sides of the equation.

8x=y-12

Divide each term in 8x=y-12 by 8.

8×8=y8+-128

Cancel the common factor of 8.

Cancel the common factor.

8×8=y8+-128

Divide x by 1.

x=y8+-128

x=y8+-128

Simplify each term.

Cancel the common factor of -12 and 8.

Factor 4 out of -12.

x=y8+4(-3)8

Cancel the common factors.

Factor 4 out of 8.

x=y8+4⋅-34⋅2

Cancel the common factor.

x=y8+4⋅-34⋅2

Rewrite the expression.

x=y8+-32

x=y8+-32

x=y8+-32

Move the negative in front of the fraction.

x=y8-32

x=y8-32

x=y8-32

Solve for x y=8x+12